(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
قمنا في هذا العمل بالتحري عن وجود بعض العناصر الكيميائية الثقيلة مثل الرصاص Pb، النحاس Cu، الزنك Zn، الكوبالت Co، النيكل Ni، المنغنيز Mn، الكروم Cr، الباريومBa ، السترونتيومSr ، الفاناديوم V، السيزيوم Cs، الكادميوم Cd، الليثيوم Li، الروبيديومRb ، اليورانيومU ، الزرنيخAs ، والزئبق Hg في الجزء الجنوبي الغربي من مدينة اللاذقية (منطقة المعامل – حي العائدين)، ومعرفة مدى ارتباط ذلك بالمواد الأولية التي تنتقل من مناطق أخرى لتستخدم في هذه المعامل، ومدى مساهمة ذلك بالتأثيرات السلبية على مختلف أنواع الحياة في هذه المنطقة وجوارها. وقد تم ذلك من خلال التعرف على بنية العينات التي أخذت من أماكن محددة من هذه المناطق، حيث أظهر التحليل الذي أجري لها أن بعض هذه العناصر موجود وفق النسب العالمية المسموح بها وأن بعضها الآخر سيصبح موجوداً وفقاً للحدود العليا لهذه النسب إذا بقي الوضع على حاله.علما" أنه تم استخدام جهازي الامتصاص الذري والأشعة السينية في تحليل العينات، وقد أجريت التحاليل كافة في مخابر كلية الزراعة في جامعة دمشق ومخابر الهيئة العامة للاستشعار عن بعد في دمشق. In this work we investigated the presence of some of the heavy chemical elements, such as Lead Pb, Copper Cu, Zinc Zn, Cobalt Co, Nickel Ni, Manganese Mn, Chromium Cr, Barium Ba, Strontium Sr, Vanadium V, Cesium Cs, Cadmium Cd, Lithium Li, Rb Rubidium , Uranium, U, Arsenic As, and Hg Mercury in the south-western part of the city of Lattakia (Mantaket Alameleen – Hay Alaedeen), and knowledge of the relevance of the raw materials that move from other areas to be used in these factories, and the extent of its contribution to the negative impacts of the various types of life in this region and its surroundings. This was done through the identification of the structure of the samples taken from specific locations of these regions, where the analysis carried out showed that some of these elements reside in the world according to the allowable ratios and others will become available in accordance with the highest of these ratios, if the situation remains unchanged. WE note that we have used two instruments: Atomic absorption and X-ray to analyze the samples, and we note that the experimental part has been realized in the laboratories of Agriculture faculty (University of Damascus) and General Organization of remote senescence (Damascus).